Mammary gland, skin and soft tissue tumors in pet cats: findings of the feline tumors collected from 2002 to 2022 - Giugliano, Roberta; Dell'Anno, Filippo; De Paolis, Livia; Crescio, Maria Ines; Ciccotelli, Valentina; Vivaldi, Barbara; Razzuoli, Elisabetta (Frontiers in Veterinary Science, 2024)
Cancer is a leading cause of death in cats, and the incidence rate of such disease has been increasing over the recently years. Nonetheless, feline oncology represents an important area of study not only for the health and wellbeing of cats, but also for human health, since many cats' cancers share similarities with human counterparts. To this purpose, epidemiological studies on feline oncology may suggest environmental and genetic factors promoting cancer in cats, which can be eventually translated to improve human cancer care. To provide an initial understanding of the epidemiology of feline neoplasms, a descriptive study was undertaken using a dataset documenting cases of feline cancer gathered from the Liguria region (north-west Italy) spanning the years 2002 to 2022. A descriptive study was conducted on a dataset reporting feline cancer case collected in the Liguria region (northwest Italy) between 2002 and 2022. The database includes tumour location, tumourmorphological codes of the ICD-O-3 origin, feline's breed, sex, neutered/spayed status, date of birth, date of diagnosis, national territorial unit code of the town of owners' residence and an alphanumeric string uniquely identifying the owners' surname. Finally, association between environmental pollution (heavy metals) and animal tumours occurrences was performed using logistic regression models. The dataset involves a population of 4399 cats including 3195 females (1425 neutered) and 1204 males (750 neutered). Our